The Effect of Leadership on the Performance of State Civil Apparatus Through Work Motivation and Job Satisfaction - Kuswanto, Dedi; Rumasukun, M. Ridwan; Khotimah, Khusnul (Jurnal Economic Resource, 2024)
The Influence of Leadership on the Performance of Civil Servants at the Regional Office of the Directorate General of Treasury of Papua Province through Work Motivation and Job Satisfaction. This study aims to examine and analyze information about the direct and indirect influence of leadership on employee performance at the Regional Office of the Directorate General of Treasury of Papua Province. The research is conducted to understand the extent to which these factors contribute to improving employee performance. The sample size of this study is 54 respondents. Data was collected through the distribution of questionnaires to the respondents. The data was analyzed using path analysis regression with IBM SPSS Statistics Version 25 as the statistical testing tool. The results of the study show that the leadership variable has a significant influence on work motivation and job satisfaction. Motivation has a significant influence on employee performance, and job satisfaction has a significant influence on employee performance. There is a significant influence of leadership on employee performance both directly and indirectly through work motivation and job satisfaction.